PERAN DAN TANGGUNG JAWAB MUSIC DIRECTOR DALAM MANAJEMEN MUSIK IBADAH RAYA - Yosia Septianus; Christanto Hadijaya; Trianus Homklom (JOURNAL of THEOLOGICAL STUDENTS, 2022)
In today's church era, music is very important in every worship activity, because good music depends on how someone processes and arranges the music into music that is pleasant to listen to. In the process of processing this music, the church really needs the power of a music director. The music director is the person who is responsible for all aspects such as leading in music management, worship activities, or directing his team because the music director himself has a very big influence in every worship activity. In the smooth process of a worship service, of course, there are important components in it, such as human resources (HR) and training for the regeneration of church musicians. Human resources are one of the important foundations in worship. If the human resources in the church are very minimal, it will certainly affect the activities in a church activity. The regeneration training for church musicians serves to prepare regenerates to enter the world of service.